The Interpreter, the Monitor and the Language Arbiter - Takeda, Kayoko (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2009)
AbstractThe trustworthiness of translators and interpreters has long been an issue in the profession. In some cases, a set of procedures are established to ensure the trust of clients and end-users. In the International Military Tribunal for the Far East (1946-1948), such procedures took on remarkable form. During the trial, three ethnically and socially different groups of language personnel engaged in three different functions within the overall interpreting process: Japanese nationals as interpreters, Japanese Americans as monitors, and U.S. military officers as language arbiters who ruled on the disputed interpretations. Sociopolitical aspects such as trust, power and control are evident in this hierarchical structure. In such political settings, and in others seen today, the trustworthiness of the interpreter may override the quality of interpreting.